Intraosseous Lipoma Occurring in the Humerus - Nishii, Akihiro; Ishinishi, Shigeru; Matsubara, Yoshihiro; Ushijima, Masahiro; Morooka, Takaaki (Orthopedics & Traumatology, 1998)
Intraosseous lipoma accounts for only 0.1% of all bone tumors. We treated a 33-year-old male with this bone tumor of the humerus. He had complaind of right shoulder pain. Radiographs of the shoulder showed a well-defined lytic lesion in right proximal humeral metaphysis. Its border was sclerotic and the lesion had a central calcific dencity. Computed tomography (CT) showed lipo-density in the aera. Magnetic resonance image (MRI), on the T1 and T2 weighted images was also compatible with adipose tissue. This tumor showed no enhancement after administration of gadolinium. Histological analysis revealed mature lipocytes. We emphasize that MRI examination is useful for preoperative diagnosis.